NILAI DALIHAN NA TOLU DALAM MEMBANGUN HIDUP BERSAMA: TINJAUAN RELASIONALITAS ARMADA RIYANTO - Lumban Gaol, Covin (Studi Budaya Nusantara, 2024)
The author focuses on the kinship system in Batak Toba culture, known as Dalihan Na Tolu. This kinship system is interpreted as identity and even serves as a guiding principle in the traditional cultural activities of Batak Toba. Dalihan Na Tolu consists of three hearthstones used for cooking. These three hearthstones are depicted as the kinship system in Batak Toba culture. The three hearthstones are Hula-hula, Dongan Tubu, and Boru. In Batak Toba culture, each person will assume one of the roles among these three elements. For the Batak people, Dalihan Na Tolu plays an important role and serves as the heart of every ceremony and relationship with others. Meanwhile, according to Armada Riyanto, self-giving transcends the relationship between "I" and "others." The research method employed by the author is a literature review involving critical analysis of various Batak culture books and previous research studies that discuss Dalihan Na Tolu. The methodology used is Armada Riyanto's relationality. This study finds that Dalihan Na Tolu is a guiding principle for Batak people in their relationships with others. This kinship system is a local cultural heritage with profound philosophical values.